Artificial Solid Electrolyte Interphase Coating to Reduce Lithium Trapping in Silicon Anode for High Performance Lithium‐Ion Batteries. Issue 21 (6th September 2019) - Ai, Qing; Li, Deping; Guo, Jianguang; Hou, Guangmei; Sun, Qing; Sun, Qidi; Xu, Xiaoyan; Zhai, Wei; Zhang, Lin; Feng, Jinkui; Si, Pengchao; Lou, Jun; et al.
Abstract: The investigation indicates that lithium trapping in Si anode of lithium‐ion battery is one of the key factors to affect the coulombic efficiency and capacity decay during high rate cycling. Here, it is demonstrated that LiAlO2 as an artificial solid electrolyte interphase (SEI) on commercial Si nanoparticles can effectively address the lithium trapping issues of Si anode to improve its electrochemical performance. By investigating the structure evolution of Si with in situ Raman and ex situ X‐ray diffraction measurements, it is demonstrated that artificial solid electrolyte interphase layer significantly improves the kinetics of lithium alloying/dealloying process due to its better electrochemical performance comparing to the natural SEI. Owing to the artificial SEI coating, the Si anode demonstrates a superior electrochemical performance, which offers a specific capacity of 1106 mAh g −1 at a current density of 4000 mA g −1 with capacity retention of 90.9% after 500 cycles. Abstract : The LiAlO2 layer has a positive effect on the lithium diffusion between electrolyte and silicon particles, which reduces the solid electrolyte interphase formation on Si particles as well as lithium trapping in Si electrode. Electrochemical performance of Si anode is dramatically improved owing to the better lithium transportation kinetics.